2005
DOI: 10.1590/s1516-89132005000600020
|View full text |Cite
|
Sign up to set email alerts
|

Morphological study of biomass during the start-up period of a fixed-bed anaerobic reactor treating domestic sewage

Abstract: This work focused on a morphological study of the microorganisms attached to polyurethane foam matrices in a horizontal-flow anaerobic immobilized biomass (HAIB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 16 publications
0
11
0
3
Order By: Relevance
“…Samples for scanning electron microscopy (SEM) were subjected to the technique developed by Nation (1983) and adapted to bacterial biofilms by Araujo (1995). The sample preparation procedures are also described in Lima et al (2005). Briefly, the samples were fixed in 0.1 M phosphate buffer (pH 7.3) containing 2.5% glutaraldehyde for 12 h at 4ºC.…”
Section: Methodsmentioning
confidence: 99%
“…Samples for scanning electron microscopy (SEM) were subjected to the technique developed by Nation (1983) and adapted to bacterial biofilms by Araujo (1995). The sample preparation procedures are also described in Lima et al (2005). Briefly, the samples were fixed in 0.1 M phosphate buffer (pH 7.3) containing 2.5% glutaraldehyde for 12 h at 4ºC.…”
Section: Methodsmentioning
confidence: 99%
“…Improvements made in the configuration of these reactors resulted in systems far more stable, controllable and with high degradation efficiency, even when operated with reduced hydraulic retention time (HRT); something attributed to elevated biomass concentrations and to greater cellular retention time (Lima et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ribas et al (2005) observed similar morphologies in granular sludge collected from an UASB. Additionally, a horizontal-flow anaerobic immobilized biomass (HAIB) reactor treating domestic sewage was found to contain rods, cocci, spirochetes, filaments, fluorescent rods and cocci as well as Methanosaeta sp.-like archaeal cells (Lima et al 2005). Hirasawa (2003) analyzed the granular sludge used in this work via FISH using the EUB338 and ARC915 probes and found that they detected 44.8% and 59.5% of the sample, respectively.…”
Section: Resultsmentioning
confidence: 95%